PIMA Handbook : Public Investment Management Assessment, 1st Edition. (International Monetary Fund, 2022)
This handbook is aimed at anyone who is involved in a Public Investment Management Assessment (PIMA) or who has a practical interest in public investment management. It is intended to be useful for country authorities, IMF staff, staff of other financial institutions and development organizations, and anyone who is interested in exploring different aspects of public investment management to understand how country systems are designed and how they work in practice.